Women farmers perception of information dissemination skills among agricultural extension workers in North Eastern Nigeria - Umar, Abdulmumini; Man, Norsida; Kamarulzaman, Nitty Hirawaty; Mohamed Haris, Nur Bahiah (Agricultural Extension Society of Nigeria, 2021)
This study examined the perception of rural women farmers on information dissemination skills of agricultural extension workers. Using multistage sampling procedure 378 respondents were randomly selected from the population of 6758 women farmers. Questionnaire was administered to the sampled farmers. Data were analysed using mean, and standard deviation. Findings reveals that women farmers participated moderately in agricultural practices with overall mean value of 2.65. Also, agricultural extension workers had a lower level of information dissemination skill in dealing with women farmers with overall mean value of 2.25. There is the need for training and retraining of extension workers to boost their skills for information delivery to women farmers. Extension programme for rural women should be designed to ensure extension workers are well informed and knowledgeable enough to work with them.